2010
DOI: 10.1007/s11626-010-9302-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of space flight and microgravity on the growth and differentiation of PICM-19 pig liver stem cells

Abstract: The PICM-19 pig liver stem cell line was cultured in space for nearly 16 d on the STS-126 mission to assess the effects of spaceflight on the liver's parenchymal cells-PICM-19 cells to differentiate into either monolayers of fetal hepatocytes or 3-dimensional bile ductules (cholangiocytes). Semi-quantitative data included light microscopic assessments of final cell density, cell morphology, and response to glucagon stimulation and electron microscopic assessment of the cells' ultrastructural features and cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…When FLSPCs were grown in 3D suspension culture, they were likely to self‐renew; in contrast, FLSPCs that were maintained in 2D adherent culture were prone to differentiation . These data are consistent with others’ report . In summary, the space and gravity factors are essential for deciding cell fates of LSPCs.…”
Section: Strategies For Inducing the Hepatic Differentiation Of Lspcssupporting
confidence: 90%
“…When FLSPCs were grown in 3D suspension culture, they were likely to self‐renew; in contrast, FLSPCs that were maintained in 2D adherent culture were prone to differentiation . These data are consistent with others’ report . In summary, the space and gravity factors are essential for deciding cell fates of LSPCs.…”
Section: Strategies For Inducing the Hepatic Differentiation Of Lspcssupporting
confidence: 90%
“…Besides, the culture of WB-F344 liver stem cells under the simulated microgravity also showed that proliferation of WB-F344 cells increases in comparison with the stationary state (Qu et al, 2007). However, no differences in cell proliferation were observed between PICM-19 pig liver stem cells cultured during a space flight (STS-126 Mission) and the cells on the ground (Talbot et al, 2010). The PICM pig liver stem cell line was cultured in space for nearly 16 days on the STS-126 mission to assess the effects of a space flight on the ability of liver parenchymal cells to differentiate into either monolayers of fetal hepatocytes or 3D bile ductules (cholangiocytes).…”
Section: Microgravity Is Beneficial For the Survival And Stemness Maimentioning
confidence: 99%
“…In the comparison between flight and ground‐control cultures 17 h after the shuttle returned to earth, no differences were found between two types of culture with the exception of some differentially expressed genes. The cells in the space flight grew to ~75% confluence and showed no signs of apoptosis or necrosis (Talbot et al, ) and either differentiated into monolayer patches of hepatocytes (with biliary canaliculi visible between cells) or into 3D bile ductules with a well‐defined lumen. Ultrastructural features of the flight and ground‐control cells were similar: PICM‐19 cells displayed numerous mitochondria, a Golgi apparatus, smooth and rough endoplasmic reticulum, vesicular bodies, and occasional lipid vacuoles.…”
Section: Microgravity Is Beneficial For the Survival And Stemness Maimentioning
confidence: 99%
“…In mesenchymal stem cells, hypergravity increased differentiation into cardiomyocytes and osteoblasts [ 3 ] whereas simulated low-gravity inhibited osteogenesis [ 4 ] and resulted in higher levels of adipogenesis [ 3 , 5 , 6 ]. Exposure of other stem cell types to simulated microgravity such as embryonic stem cells [ 7 ], umbilical cord blood stem cells [ 8 ], adipose-derived stem cells [ 9 ], liver stem cells [ 10 ], and cancer stem cells [ 11 ] have established a link between gravitational force and changes in cell identity, either towards stemness or differentiation.…”
Section: Introductionmentioning
confidence: 99%